1981
DOI: 10.1111/j.1471-4159.1981.tb01624.x
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Interaction of S‐100 Protein with Synaptosomal Particulate Fractions. Evidence for the Formation of a Tight Complex Between S‐100 and Its Binding Sites

Abstract: The dissociation of the 125I-labelled S-100 specifically bound to synaptosomal particulate fractions (SYN) has been studied under a variety of conditions after different association times. The results indicate that after a critical association time of about 20 min at 37 degrees C, the bound protein becomes progressively less accessible to the dissociating agents of conditions employed. These findings support the view that the partial irreversibility of the 125I-labelled S-100 binding to SYN could be due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

1982
1982
1986
1986

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
2
9
0
1
Order By: Relevance
“…They indicated that: (a) membrane-bound (endogenous) Ca2+ and/or other divalent cations are essential for full expression of the high-affinity sites; (b) s-100 binding is sensitive to the ionic strength of the medium, as evidenced by the striking decrease of the extent of the binding with no change of the apparent affinity observed with 1M NaCl in the incubation medium; and (c) the Ca2+ conformation of S-100 (Calissano et al, 1976) is as important as the proper conformation of the binding molecule(s) for the high-affinity sites to be activated, as evidenced by the profound effect of the presence of 0.2M KC1 in the incubation medium. These data also indicated that forces other than ionic interactions contribute to the S-100 binding to SYN, as suggested elsewhere (Donato, 1981). In this connection, the role played by membrane lipids (Donato, 19766) was further emphasized by the inhibition of highaffinity 5-100 binding observed with SYN pretreated with either phospholipase C or D. In particular, the polar head groups of membrane phospholipids appear to be essential for S-100 to bind to SYN with high affinity.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…They indicated that: (a) membrane-bound (endogenous) Ca2+ and/or other divalent cations are essential for full expression of the high-affinity sites; (b) s-100 binding is sensitive to the ionic strength of the medium, as evidenced by the striking decrease of the extent of the binding with no change of the apparent affinity observed with 1M NaCl in the incubation medium; and (c) the Ca2+ conformation of S-100 (Calissano et al, 1976) is as important as the proper conformation of the binding molecule(s) for the high-affinity sites to be activated, as evidenced by the profound effect of the presence of 0.2M KC1 in the incubation medium. These data also indicated that forces other than ionic interactions contribute to the S-100 binding to SYN, as suggested elsewhere (Donato, 1981). In this connection, the role played by membrane lipids (Donato, 19766) was further emphasized by the inhibition of highaffinity 5-100 binding observed with SYN pretreated with either phospholipase C or D. In particular, the polar head groups of membrane phospholipids appear to be essential for S-100 to bind to SYN with high affinity.…”
Section: Discussionsupporting
confidence: 73%
“…1, and of a curvilinear concave downwards component, corresponding to the second phase of the same curve. This, however, could not be employed for calculating the usual binding parameters, i.e., the binding capacity and the dissociation constant, owing to both the partial irreversibility of S-100 binding ti, SYN (Donato, 1981) and the presence of the two concavities in the plot itself. With these limitations in mind, and taking into account the results of competition experiments in the presence of S-100a and S-100b ( Fig.…”
Section: Binding Studies At Apparent Equilibriummentioning
confidence: 99%
“…These latter include the nonspecific adsorption of anti-S-100 antisera and inadequate fixation that may result in the diffusion of this soluble, low molecular weight protein out of the cytoplasm. In this context we may note that S-100 has been shown to bind to synaptosomes and to glial nuclei in vitro (36,37). We feel confident, however, that with adequate fixation the monoclonal antibody G12.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, S-100 seems to behave both as a soluble and an integral membrane protein, as is the case with calmodulin (Sobue et al, 1981) and tubulin (Bhattacharyya and Wolff, 1975), though we cannot exclude the possibility that membrane-bound S-100 is tightly associated with one or more integral membrane proteins. In effect, cytoplasmic S-100 has the capacity to interact in vitro with high-affinity binding sites in a restricted number of natural membranes in the presence of Ca2+ (Donato, 19836 and references therein), forming a tight complex with these sites after a critical association time (Donato, 1981), and to modify the physical state of the lipid bilayer of membranes on binding to these (Curatola et al, 1985). The S-100 binding sites seem to be protein in nature, though membrane lipids seem to play a role in the interaction (Donato, 19836).…”
Section: Resultsmentioning
confidence: 99%